Pengaruh Debt to Equity Ratio Terhadap Return on Assets pada PT Kalbe Farma TBK. Periode 2017-2024 - Ellenora Deanne Setiawan; Mariana Cyntia Kustiawan; Elizabeth Tiur Manurung (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This research is driven by the significance of managing capital structure to improve a company's profitability, particularly at PT Kalbe Farma Tbk, one of Indonesia’s leading pharmaceutical companies. The aim of this research is to examine the impact of the Debt to Equity Ratio (DER) on Return on Assets (ROA) over the period 2017–2024. A quantitative approach was employed using simple linear regression analysis based on the company’s quarterly financial data. The results indicate that DER has a negative and significant effect on ROA, with a regression coefficient of -0.410 and a p-value of 0.0126, which is less than the 0.05 significance level. The R² value of 18.99% suggests that DER accounts for 18.99% of the variation in ROA. In conclusion, an increase in DER tends to reduce ROA, emphasizing the need for the company to maintain a balanced capital structure to sustain financial performance.